BENCHMARKING MANUFACTURING PERFORMANCE IN THE SEMICONDUCTOR INDUSTRY - BENSON, ROBERT F.; CUNNINGHAM, SEAN P.; LEACHMAN, ROBERT C. (Production and Operations Management, 1995)
A methodology for benchmarking manufacturing practices in the worldwide semiconductor industry is presented. Several metrics for measuring semiconductor manufacturing performance are defined and discussed. Interviews conducted during site visits are used to identify the managerial, technical, and organizational practices underlying superior metric performance. Multivariate statistical analyses of the performance metric data indicate that these performance metrics measure independent aspects of performance and expose significant performance differences among fabs.